Empowering patient education on self-care activity among patients with colorectal cancer - a research protocol for a randomised trial - Leena Tuominen; Marita Ritmala-Castrén; Pia Nikander; Siru Mäkelä; Tero Vahlberg; Helena Leino-Kilpi (BMC, 2021)
Abstract Background Chemotherapy-induced side effects may have a negative effect on nutrition intake, thus increasing the risk of malnutrition and consequently, other serious complications for patients with cancer. The prevalence of malnutrition is common among patients with colorectal cancer. Nurse-led empowering education may have a positive effect on self-care activity in this patient group. Therefore, our purpose is to develop an empowering educational nursing intervention and test its effect on self-care activation and knowledge level among patients with colorectal cancer during chemotherapy. Secondary outcomes are quality of life and risk of malnutrition. Methods An interdisciplinary expert group developed a face-to-face empowering educational intervention using teach-back method. A two-arm, single-centre, superiority trial with stratified randomisation (1:1) and pre-post measures will be used to assess the effect of the intervention compared to standard care. Patients (N = 40 + 40) will be recruited in one university hospital outpatient clinic in Finland. Eligibility criteria are adult patients diagnosed with colorectal cancer starting oral fluoropyrimidine or combination chemotherapy treatment. A registered nurse experienced in oncology will deliver the intervention 2 weeks after the first chemotherapy. Outcomes are measured before intervention (M0) and after a two-month follow-up period (M1). Discussion This study will assess whether nurse-led empowering education using teach-back method is effective on self-care activity among patients with colorectal cancer. If the intervention has a positive effect, it may be implemented into patient education in a corresponding context. Trial registration ClinicalTrials.gov : NCT04160650 Registered 12 November 2019 - retrospectively registered